Esterase variability in the populations of culex quinquefasciatus say 1823 from two geographically isolated locations in Bangladesh - Shahjahan, Reza Md; Begum, Rowshan Ara; Rumman, Marufa; Karim, Farhana Sultana; Begum, Anwara (Dhaka University Journal of Biological Sciences, 2011)
Indiscriminate and frequent use of insecticides are causing occurrence of resistance problem in the treated population in mosquitoes. Organo-phosphates are associated with esterase enzyme overproduction leading towards the selection of resistant population. Esterase pattern was studied from two geographically isolated populations of Culex quinquefasciatus by the Polyacrylamide Gel Electrophoresis (PAGE). The municipal area of Sirajganj (24°19'48" N, 89°37'12"E) is located 160 km away from Dhaka (23°42'0" N, 90°22'30"E), the capital of Bangladesh. In Dhaka insecticides are frequently sprayed with by the city corporation whereas in Sirajganj town insecticides usually not in use. Altogether eight and seven esterase bands were observed from above two populations. These were named as Est-1, Est-2, Est-3, Est-4, Est-5 Est-6, Est-7, Est-8, respectively. Sirajganj population in general showed less esterase activity in comparison with that of Hatirjheel. Est-5 in Hatirjheel population was found to be distinct and darkly stained. These reflect increasing insecticide resistance due to excessive use of insecticides in mosquito control program in the Dhaka city. Furthermore, in Sirajganj population two female samples were found to produce unique bands in Est-2, very thick (~50-100fold), although these specimens were morphologically similar to other samples, alleged to be the occurrence of species complex in Culex quinquefasciatus. Nation wide intensive sampling and large scale study in terms of esterase appears to be essential to reveal the entity of species complex and correlate resistance with the esterases for managerial purpose. Key Words: Esterase variability; Culex quinquefasciatus; Isolated locations DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8939 DUJBS 2010; 19(1): 13-20